Technology, communication, disparities and government options in health and health care services - Kronenfeld, Jennie J. (Bingley, U.K. : Emerald, 2014)
This volume includes papers related to issues of technology, communication, health disparities and government options in health and health care services. It fills an existing gap by providing a clear sociological overview and focus on these topics. Technology is considered from the perspectives of providing healthcare equity, health disparities and the impact on doctor-patient relationships. The topic of communication is addressed in the format of public health messages and the use of internet chat rooms for discussions about health care services. Government roles and responsibilities are reflected upon in terms of health promotion, marketing and sales of health-related products and improving long-term care programs. Particular mention is made to learning lessons from the experiences and perspectives of other countries. Finally, health disparities are considered in socioeconomic terms, with particular reference to aging, depression, measures of health and healthcare in rural locations.
Technology, communications, government roles and health disparities / Jennie Jacobs Kronenfeld -- Can information technology improve healthcare equity in the United States? Lessons from Taiwan / Claudia Chaufan and Yi-Chang Li -- Patterns of online health searching 2002-2010 : implications for social capital, health disparities and the de-professionalization of medical knowledge / Timothy M. Hale ... [et al.] -- The implementation of public health communication messages to promote teenage mothers' sense of self and avert stigma / Neale R. Chumbler, Helen Sanetmatsu and John Parrish-Sprowl -- Virtual health : the impact of health-related websites on patient-doctor interactions / Scott V. Savage, Samantha Kwan and Kelly Bergstrand -- Reject, delay, or consent? Parents' internet discussions of the HPV vaccine for children and implications for HPV vaccine uptake / Kathy Livingston, Kathleen M. Sutherland and Lauren M. Sardi -- Determinants in Norwegian local government health promotion institutional perspectives / Marit Helgesen and Hege Hofstad -- Social implications of long term care insurance in Japan : a review / Atsuko Kawakami -- Harm to the health of the public arising from aggressive marketing and sales of health-related products and services : another aspect of medicalization which is a cause for concern? / Kai-Lit Phua -- Improving resident outcomes in state Medicaid nursing facility long-term care programs : augmenting CMS surveys with modest changes to a few state program features / Charles Lockhart ... [et al.] -- Fundamental causes of health disparities : associations between adverse socioeconomic resources and multiple measures of health / Katie Kerstetter and John J. Green -- Predictors of rural health clinics managers' willingness to join accountable care organizations / Thomas T.H. Wan, Maysoun Dimachkie Masri and Judith Ortiz -- Aging Puerto Ricans experiences of depression treatment : a new ethnographic exploration / Marta B. Rodríguez-Galán, Luis M. Falcón.
Print version record
Keywords: Social Science -- Disease & Health Issues; Social Science -- Ethnic Studies -- General; General practice; Personal & public health; Public health -- Social aspects; Communication in public health